Clinical efficacy and safety of acupuncture in modulating autonomic nervous function: a meta-analysis of randomized controlled trials - Ma, Ying-zhi; Zhang, Pu-yao; Du, Tao; Wang, Zi-chen; Wang, Tian-duo; Fu, Ai-hui; Wang, Zhao-mei-zi; Ma, Tie-ming; Zhang, Wei (Frontiers in Neuroscience, 2025)
BackgroundThe autonomic nervous system (ANS) plays a pivotal role in maintaining physiological homeostasis, and its dysfunction is implicated in various chronic disorders. Current pharmacological and neuromodulatory interventions are constrained by limitations such as adverse effects and invasiveness. Acupuncture, a cornerstone of complementary and alternative medicine (CAM), demonstrates potential for bidirectionally modulating ANS function, yet systematic evidence remains scarce.MethodsA meta-analysis was conducted on randomized controlled trials (RCTs) retrieved from PubMed, Embase, CNKI, Wanfang, and CENTRAL databases from their inception until 1 August 2025. Data on baseline characteristics, heart rate variability (HRV) parameters (standard deviation of normal-to-normal intervals (SDNN), low frequency (LF), high frequency (HF), LF/HF), and adverse events were extracted. Analyses were performed using random-effects models.ResultsTen RCTs comprising 744 patients were included. Acupuncture significantly improved SDNN. True effect sizes for LF and HF suggested potential differences, but considerable uncertainty was evident. The incidence of adverse events was low, with no serious events reported.ConclusionAcupuncture may confer modest improvements in ANS function, particularly evidenced by SDNN enhancement, and exhibits a favorable safety profile. However, the evidence is constrained by heterogeneity and methodological limitations, necessitating further validation through high-quality studies.